TEACHING NARRATIVES IN THE 2020 PANDEMIC: CHALLENGES, LEARNINGS AND SUBJECTIVITIES - Sousa Silva Muraro, Juliane de; Gomes, Alberto Albuquerque [UNESP] (Univ Federal Mato Grosso Sul, 2023)
The article is based on a set of excerpts extracted from letters received from teachers of basic education in the state public network of Sao Paulo in the year 2021. Thus, we will present a reflection on the challenges, learning and subjectivities of teachers in the context of the pandemic in 2020. As procedures, we sent a letter to a group of basic education teachers in which we asked them to tell us how they have faced the situation created by the Covid-19 pandemic, which has affected the whole of society, including the school. We asked them to detail the impact of this new normal, feelings derived from it, the actions taken in dealing with this new context and their impressions on how school and state managers have managed such issues. Some of the reports contained in the letters pointed out the following aspects: 1. the surprise and insecurity among the teachers; 2. the resilience and empathy that have characterized the actions of the teachers of this school for the mutual reception and of the parents and students who have been hard hit; 3. several difficulties have been observed in dealing with technological instruments that were not part of the teachers' daily lives; 4. favorable expectations for the outcome of this pandemic and future practices in the school context. We conclude that there were many difficulties faced by teachers when dealing with the teaching and learning process in the context of the pandemic, but these obstacles were overcome, so that the importance of the teaching role and the school as a space for exchanges and diffusion was reaffirmed. of knowledge.
Keywords: Pandemic; Technology; Narratives; Resilience